PENGARUH DISIPLIN KERJA DAN ETOS KERJA TERHADAP EFETIVITAS KERJA PEGAWAI PADA PT. POS INDONESIA - Fairuz, Muhammad Fawad (JURNAL EKONOMI AKUNTANSI MANAJEMEN AGRIBISNIS, 2023)
Post is a State-Owned Enterprise. Looking at the background of the problem in this research is the researcher's reason that PT. Pos Indonesia experienced problems with work discipline and work ethic which had an impact on employee work effectiveness. The research method used was survey. The research instrument was in the form of distributing questionnaires. The sample size in this study was 48 respondents. Data analysis used in this research was Validity test, Reliability test, Classic Assumption test, Multiple linear regression test, Hypothesis test and Coefficient of Determination test. The results of the t test show that the tcount for the Work Discipline variable is (6.556) while the ttable value is (2.010), so it is known that tcount > ttable with a significance value of 0.000 < α = 0.005. The influence of work ethic on employee work effectiveness from the results of the t test shows that the work ethic variable is (-0.782) while the ttable value is (2.010), so it can be seen that tcount < ttable with a significance value of 0.439 > α = 0.05. The influence of work ethic and work discipline simultaneously has a significant effect on employee work effectiveness. It can be seen that the Fcount value is 29.013 > Ftable 3.20 with a significance level of 0.000 < α = 0.05. Based on the research conducted in this study, it can be concluded that work discipline and work ethic have a significant effect on the work effectiveness of PT employees. Pos Indonesia partially or simultaneously.